A comprehensive review on electrospun nanohybrid membranes for wastewater treatment - Kumarage, Senuri; Munaweera, Imalka; Kottegoda, Nilwala (Beilstein Journal of Nanotechnology, 2022)
Electrospinning, being a versatile and straightforward method to produce nanofiber membranes, has shown significant advancement in recent years. On account of the unique properties such as high surface area, high porosity, mechanical strength, and controllable surface morphologies, electrospun nanofiber membranes have been found to have a great potential in many disciplines. Pure electrospun fiber mats modified with different techniques of surface modification and additive incorporation have exhibited enhanced properties compared to traditional membranes and are even better than the as-prepared electrospun membranes. In this review, we have summarized recently developed electrospun nanohybrids fabricated by the incorporation of functional specific nanosized additives to be used in various water remediation membrane techniques. The adsorption, filtration, photocatalytic, and bactericidal capabilities of the hybrid membranes in removing common major water pollutants such as metal ions, dyes, oils, and biological pollutants have been discussed. Finally, an outlook on the future research pathways to fill the gaps existing in water remediation have been suggested.
Keywords: electrospinning; environmental remediation; membrane technologies; nanohybrids; water purification

(untitled) - Lalia, B. S.; Kochkodan, V.; Hashaikeh, R.; Hilal, N. (Desalination, 2013)

(untitled) - Ray, S. S.; Chen, S.-S.; Li, C.-W.; Nguyen, N. C.; Nguyen, H. T. (RSC Adv., 2016)

(untitled) - Dai, X.; Li, X.; Zhang, M.; Xie, J.; Wang, X. (ACS Omega, 2018)

(untitled) - Qiao, Z.; Shen, M.; Xiao, Y.; Zhu, M.; Mignani, S.; Majoral, J.-P.; Shi, X. (Coord. Chem. Rev., 2018)

(untitled) - Feng, C.; Khulbe, K. C.; Matsuura, T.; Tabe, S.; Ismail, A. F. (Sep. Purif. Technol., 2013)

(untitled) - Esfahani, H.; Jose, R.; Ramakrishna, S. (Materials, 2017)

(untitled) - Suja, P. S.; Reshmi, C. R.; Sagitha, P.; Sujith, A. (Polym. Rev. (Philadelphia, PA, U. S.), 2017)

(untitled) - Giuri, D.; Barbalinardo, M.; Sotgiu, G.; Zamboni, R.; Nocchetti, M.; Donnadio, A.; Corticelli, F.; Valle, F.; Gennari, C. G. M.; Selmin, F.; Posati, T.; Aluigi, A. (Nanoscale, 2019)

(untitled) - Patel, D. K.; Dutta, S. D.; Hexiu, J.; Ganguly, K.; Lim, K.-T. (Int. J. Biol. Macromol., 2020)

(untitled) - Munaweera, I.; Aliev, A.; Balkus, K. J., Jr (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Munaweera, I.; Levesque-Bishop, D.; Shi, Y.; Di Pasqua, A. J.; Balkus, K. J., Jr (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Bugatti, V.; Vertuccio, L.; Viscusi, G.; Gorrasi, G. (Nanomaterials, 2018)

(untitled) - Zhang, S.; Li, D.; Kang, J.; Ma, G.; Liu, Y. (J. Appl. Polym. Sci., 2018)

(untitled) - Zhang, J.; Xiang, Y.; Jamil, M. I.; Lu, J.; Zhang, Q.; Zhan, X.; Chen, F. (J. Membr. Sci., 2018)

(untitled) - Savva, I.; Kalogirou, A. S.; Achilleos, M.; Vasile, E.; Koutentis, P. A.; Krasia-Christoforou, T. (Molecules, 2016)

(untitled) - Ge, J. C.; Choi, N. J. (Nanomaterials, 2017)

(untitled) - Al-Attabi, R.; Morsi, Y.; Kujawski, W.; Kong, L.; Schütz, J. A.; Dumée, L. F. (Sep. Purif. Technol., 2019)

Electrospinning Technology for Nanofibrous Scaffolds in Tissue Engineering - Li, W.-J.; Shanti, R. M.; Tuan, R. S. (Wiley-VCH Verlag GmbH, 2007)

(untitled) - Liao, Y.; Loh, C.-H.; Tian, M.; Wang, R.; Fane, A. G. (Prog. Polym. Sci., 2018)

Handbook of nanofibers - Alghoraibi, I.; Alomari, S. (Different methods for nanofiber design and fabrication, 2019)

(untitled) - Demir, M. M.; Yilgor, I.; Yilgor, E.; Erman, B. (Polymer, 2002)

(untitled) - Huan, S.; Liu, G.; Han, G.; Cheng, W.; Fu, Z.; Wu, Q.; Wang, Q. (Materials, 2015)

(untitled) - Liu, Z.; Ju, K.; Wang, Z.; Li, W.; Ke, H.; He, J. (Nanoscale Res. Lett., 2019)

(untitled) - Kim, J.-H.; Lee, J.-H.; Kim, J.-Y.; Kim, S. S. (Appl. Sci., 2018)

(untitled) - Nurwaha, D.; Han, W.; Wang, X. (J. Text. Inst., 2013)

(untitled) - Megelski, S.; Stephens, J. S.; Chase, D. B.; Rabolt, J. F. (Macromolecules, 2002)

(untitled) - Teo, W. E.; Ramakrishna, S. (Nanotechnology, 2006)

(untitled) - Ren, L.-F.; Xia, F.; Shao, J.; Zhang, X.; Li, J. (Desalination, 2017)

(untitled) - Sencadas, V.; Correia, D. M.; Areias, A.; Botelho, G.; Fonseca, A. M.; Neves, I. C.; Gomez Ribelles, J. L.; Lanceros Mendez, S. (Carbohydr. Polym., 2012)

(untitled) - Macossay, J.; Marruffo, A.; Rincon, R.; Eubanks, T.; Kuang, A. (Polym. Adv. Technol., 2007)

(untitled) - Sadat-Shojai, M. (J. Mater. Sci. Technol., 2016)

(untitled) - Subrahmanya, T. M.; Arshad, A. B.; Lin, P. T.; Widakdo, J.; Makari, H. K.; Austria, H. F. M.; Hu, C.-C.; Lai, J.-Y.; Hung, W.-S. (RSC Adv., 2021)

(untitled) - Deitzel, J. M.; Kleinmeyer, J.; Harris, D.; Beck Tan, N. C. (Polymer, 2001)

(untitled) - Fong, H.; Chun, I.; Reneker, D. H. (Polymer, 1999)

(untitled) - Nezarati, R. M.; Eifert, M. B.; Cosgriff-Hernandez, E. (Tissue Eng., Part C, 2013)

(untitled) - Lasprilla-Botero, J.; Álvarez-Láinez, M.; Lagaron, J. M. (Mater. Today Commun., 2018)

(untitled) - Lin, J.; Ding, B.; Yu, J. (ACS Appl. Mater. Interfaces, 2010)

(untitled) - Putti, M.; Simonet, M.; Solberg, R.; Peters, G. W. M. (Polymer, 2015)

(untitled) - Touny, A. H.; Lawrence, J. G.; Jones, A. D.; Bhaduri, S. B. (J. Mater. Res., 2010)

(untitled) - Angammana, C. J.; Jayaram, S. H. (IEEE Trans. Ind. Appl., 2011)

(untitled) - Uyar, T.; Besenbacher, F. (Polymer, 2008)

(untitled) - Pelipenko, J.; Kristl, J.; Janković, B.; Baumgartner, S.; Kocbek, P. (Int. J. Pharm., 2013)

(untitled) - De Vrieze, S.; Van Camp, T.; Nelvig, A.; Hagström, B.; Westbroek, P.; De Clerck, K. (J. Mater. Sci., 2009)

(untitled) - Huang, L.; Bui, N.-N.; Manickam, S. S.; McCutcheon, J. R. (J. Polym. Sci., Part B: Polym. Phys., 2011)

(untitled) - Medeiros, E. S.; Mattoso, L. H. C.; Offeman, R. D.; Wood, D. F.; Orts, W. J. (Can. J. Chem., 2008)

(untitled) - Lu, P.; Xia, Y. (Langmuir, 2013)

(untitled) - Pakravan, M.; Heuzey, M.-C.; Ajji, A. (Polymer, 2011)

Production of chitosan-based non-woven membranes using the electrospinning process - Lonbani, M. P. (École Polytechnique de Montréa, 2012)

(untitled) - Kaur, S.; Sundarrajan, S.; Rana, D.; Sridhar, R.; Gopal, R.; Matsuura, T.; Ramakrishna, S. (J. Mater. Sci., 2014)

(untitled) - Essalhi, M.; Khayet, M. (J. Membr. Sci., 2014)

Advanced Technologies - Ravanchi, M. T.; Kargari, A. (New Advances in Membrane Technology, 2009)

(untitled) - Van Der Bruggen, B.; Vandecasteele, C.; Van Gestel, T.; Doyen, W.; Leysen, R. (Environ. Prog., 2003)

(untitled) - Wang, X.; Hsiao, B. S. (Curr. Opin. Chem. Eng., 2016)

(untitled) - Tai, M. H.; Gao, P.; Tan, B. Y. L.; Sun, D. D.; Leckie, J. O. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Wang, R.; Zhang, L.; Chen, B.; Zhu, X. (J. Membr. Sci., 2020)

(untitled) - Su, Q.; Zhang, J.; Zhang, L.-Z. (Desalination, 2020)

(untitled) - Kim, H.-C.; Choi, B. G.; Noh, J.; Song, K. G.; Lee, S.-h.; Maeng, S. K. (Desalination, 2014)

(untitled) - Feng, Q.; Wu, D.; Zhao, Y.; Wei, A.; Wei, Q.; Fong, H. (J. Hazard. Mater., 2018)

(untitled) - Brandes, R.; Belosinschi, D.; Brouillette, F.; Chabot, B. (J. Environ. Chem. Eng., 2019)

(untitled) - Surgutskaia, N. S.; Martino, A. D.; Zednik, J.; Ozaltin, K.; Lovecká, L.; Bergerová, E. D.; Kimmer, D.; Svoboda, J.; Sedlarik, V. (Sep. Purif. Technol., 2020)

(untitled) - Li, L.; Wang, F.; Lv, Y.; Liu, J.; Bian, H.; Wang, W.; Li, Y.; Shao, Z. (ACS Omega, 2018)

(untitled) - Yari, S.; Abbasizadeh, S.; Mousavi, S. E.; Moghaddam, M. S.; Moghaddam, A. Z. (Process Saf. Environ. Prot., 2015)

(untitled) - Talebi, M.; Abbasizadeh, S.; Keshtkar, A. R. (Process Saf. Environ. Prot., 2017)

(untitled) - Aliahmadipoor, P.; Ghazanfari, D.; Gohari, R. J.; Akhgar, M. R. (RSC Adv., 2020)

(untitled) - Ivshina, I. B.; Kuyukina, M. S.; Krivoruchko, A. V.; Elkin, A. A.; Makarov, S. O.; Cunningham, C. J.; Peshkur, T. A.; Atlas, R. M.; Philp, J. C. (Environ. Sci.: Processes Impacts, 2015)

(untitled) - Peng, Y.; Guo, Z. (J. Mater. Chem. A, 2016)

(untitled) - Obaid, M.; Barakat, N. A. M.; Fadali, O. A.; Motlak, M.; Almajid, A. A.; Khalil, K. A. (Chem. Eng. J., 2015)

(untitled) - Zhang, P.; Tian, R.; Lv, R.; Na, B.; Liu, Q. (Chem. Eng. J., 2015)

(untitled) - Ge, J.; Zhang, J.; Wang, F.; Li, Z.; Yu, J.; Ding, B. (J. Mater. Chem. A, 2017)

(untitled) - Shang, Y.; Si, Y.; Raza, A.; Yang, L.; Mao, X.; Ding, B.; Yu, J. (Nanoscale, 2012)

(untitled) - Ma, W.; Zhang, Q.; Samal, S. K.; Wang, F.; Gao, B.; Pan, H.; Xu, H.; Yao, J.; Zhan, X.; De Smedt, S. C.; Huang, C. (RSC Adv., 2016)

(untitled) - Jiang, Z.; Tijing, L. D.; Amarjargal, A.; Park, C. H.; An, K.-J.; Shon, H. K.; Kim, C. S. (Composites, Part B, 2015)

(untitled) - Reshmi, C. R.; Sundaran, S. P.; Juraij, A.; Athiyanathil, S. (RSC Adv., 2017)

(untitled) - Shanker, U.; Rani, M.; Jassal, V. (Environ. Chem. Lett., 2017)

Organic Pollutants Ten Years After the Stockholm Convention - Environmental and Analytical Update - Carmen, Z.; Daniela, S. (Textile Organic Dyes – Characteristics, Polluting Effects and Separation/Elimination Procedures from Industrial Effluents – A Critical Overview, 2012)

(untitled) - Hosseini, S. A.; Vossoughi, M.; Mahmoodi, N. M.; Sadrzadeh, M. (J. Cleaner Prod., 2018)

(untitled) - Hosseini, S. A.; Vossoughi, M.; Mahmoodi, N. M.; Sadrzadeh, M. (Appl. Clay Sci., 2019)

(untitled) - Gopi, S.; Balakrishnan, P.; Pius, A.; Thomas, S. (Carbohydr. Polym., 2017)

(untitled) - Huong, D. T. M.; Chai, W. S.; Show, P. L.; Lin, Y.-L.; Chiu, C.-Y.; Tsai, S.-L.; Chang, Y.-K. (Int. J. Biol. Macromol., 2020)

(untitled) - Hou, C.; Jiao, T.; Xing, R.; Chen, Y.; Zhou, J.; Zhang, L. (J. Taiwan Inst. Chem. Eng., 2017)

(untitled) - Liu, Y.; Hou, C.; Jiao, T.; Song, J.; Zhang, X.; Xing, R.; Zhou, J.; Zhang, L.; Peng, Q. (Nanomaterials, 2018)

(untitled) - Zeng, G.; He, Y.; Zhan, Y.; Zhang, L.; Pan, Y.; Zhang, C.; Yu, Z. (J. Hazard. Mater., 2016)

(untitled) - Yin, H.; Zhao, J.; Li, Y.; Huang, L.; Zhang, H.; Chen, L. (J. Cleaner Prod., 2020)

(untitled) - Sundaran, S. P.; Reshmi, C. R.; Sagitha, P.; Manaf, O.; Sujith, A. (J. Environ. Manage., 2019)

(untitled) - Ma, F.-f.; Zhang, D.; Huang, T.; Zhang, N.; Wang, Y. (Chem. Eng. J., 2019)

(untitled) - Li, L.; Wang, F.; Lv, Y.; Liu, J.; Zhang, D.; Shao, Z. (Appl. Clay Sci., 2018)

(untitled) - Min, L.-L.; Yang, L.-M.; Wu, R.-X.; Zhong, L.-B.; Yuan, Z.-H.; Zheng, Y.-M. (J. Colloid Interface Sci., 2019)

(untitled) - Shariful, M. I.; Sepehr, T.; Mehrali, M.; Ang, B. C.; Amalina, M. A. (J. Appl. Polym. Sci., 2018)

(untitled) - Homaeigohar, S.; Zillohu, A. U.; Abdelaziz, R.; Hedayati, M. K.; Elbahri, M. (Materials, 2016)

(untitled) - Habiba, U.; Siddique, T. A.; Li Lee, J. J.; Joo, T. C.; Ang, B. C.; Afifi, A. M. (Carbohydr. Polym., 2018)

(untitled) - Habiba, U.; Afifi, A. M.; Salleh, A.; Ang, B. C. (J. Hazard. Mater., 2017)

(untitled) - Zhang, W.; Yang, P.; Li, X.; Zhu, Z.; Chen, M.; Zhou, X. (Int. J. Biol. Macromol., 2019)

(untitled) - Gao, Q.; Luo, J.; Wang, X.; Gao, C.; Ge, M. (Nanoscale Res. Lett., 2015)

(untitled) - Stanly, S.; Jelmy, E. J.; John, H. (J. Polym. Environ., 2020)

(untitled) - Chen, H.; Lin, J.; Zhang, N.; Chen, L.; Zhong, S.; Wang, Y.; Zhang, W.; Ling, Q. (J. Hazard. Mater., 2018)

(untitled) - Li, Y.; Zhao, R.; Chao, S.; Sun, B.; Wang, C.; Li, X. (Chem. Eng. J., 2018)

(untitled) - Tu, H.; Huang, M.; Yi, Y.; Li, Z.; Zhan, Y.; Chen, J.; Wu, Y.; Shi, X.; Deng, H.; Du, Y. (Appl. Surf. Sci., 2017)

(untitled) - Anis, S. F.; Hashaikeh, R.; Hilal, N. (J. Water Process Eng., 2019)

(untitled) - Gao, W.; Liang, H.; Ma, J.; Han, M.; Chen, Z.-l.; Han, Z.-s.; Li, G.-b. (Desalination, 2011)

(untitled) - Anand, A.; Unnikrishnan, B.; Mao, J.-Y.; Lin, H.-J.; Huang, C.-C. (Desalination, 2018)

(untitled) - Moradi, G.; Rajabi, L.; Dabirian, F.; Zinadini, S. (J. Appl. Polym. Sci., 2018)

(untitled) - Moradi, G.; Zinadini, S.; Dabirian, F.; Rajabi, L. (Sep. Purif. Technol., 2019)

(untitled) - Zhang, J.; Xue, Q.; Pan, X.; Jin, Y.; Lu, W.; Ding, D.; Guo, Q. (Chem. Eng. J., 2017)

(untitled) - Islam, M. S.; McCutcheon, J. R.; Rahaman, M. S. (J. Membr. Sci., 2017)

(untitled) - Jang, W.; Yun, J.; Jeon, K.; Byun, H. (RSC Adv., 2015)

(untitled) - Goetz, L. A.; Jalvo, B.; Rosal, R.; Mathew, A. P. (J. Membr. Sci., 2016)

(untitled) - Pishnamazi, M.; Koushkbaghi, S.; Hosseini, S. S.; Darabi, M.; Yousefi, A.; Irani, M. (J. Mol. Liq., 2020)

(untitled) - Al-Husaini, I. S.; Yusoff, A. R. M.; Lau, W. J.; Ismail, A. F.; Al-Abri, M. Z.; Al-Ghafri, B. N.; Wirzal, M. D. H. (Sep. Purif. Technol., 2019)

(untitled) - Zhijiang, C.; Cong, Z.; Ping, X.; Jie, G.; Kongyin, Z. (J. Mater. Sci., 2018)

(untitled) - Karunanidhi, A.; David, P. S.; Fathima, N. N. (Water, Air, Soil Pollut., 2020)

(untitled) - Malaeb, L.; Ayoub, G. M. (Desalination, 2011)

(untitled) - Ghosh, A. K.; Hoek, E. M. V. (J. Membr. Sci., 2009)

(untitled) - Wang, X.; Ma, H.; Chu, B.; Hsiao, B. S. (Desalination, 2017)

(untitled) - Yang, Y.; Xu, Y.; Liu, Z.; Huang, H.; Fan, X.; Wang, Y.; Song, Y.; Song, C. (J. Membr. Sci., 2020)

(untitled) - Pan, S.-F.; Ke, X.-X.; Wang, T.-Y.; Liu, Q.; Zhong, L.-B.; Zheng, Y.-M. (Ind. Eng. Chem. Res., 2019)

(untitled) - Tian, M.; Wang, Y.-N.; Wang, R.; Fane, A. G. (Desalination, 2017)

(untitled) - Zhang, C.; Huang, M.; Meng, L.; Li, B.; Cai, T. (J. Chem. Technol. Biotechnol., 2017)

(untitled) - Obaid, M.; Ghouri, Z. K.; Fadali, O. A.; Khalil, K. A.; Almajid, A. A.; Barakat, N. A. M. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Obaid, M.; Kang, Y.; Wang, S.; Yoon, M.-H.; Kim, C.-M.; Song, J.-h.; Kim, I. S. (J. Mater. Chem. A, 2018)

(untitled) - Woo, Y. C.; Kim, Y.; Shim, W.-G.; Tijing, L. D.; Yao, M.; Nghiem, L. D.; Choi, J.-S.; Kim, S.-H.; Shon, H. K. (J. Membr. Sci., 2016)

(untitled) - Koo, J.; Nam, S.-H.; Kim, E.; Hwang, T.-M.; Lee, S. (Desalin. Water Treat., 2017)

(untitled) - Mericq, J.-P.; Laborie, S.; Cabassud, C. (Chem. Eng. J., 2011)

(untitled) - Sarbatly, R.; Chiam, C.-K. (Appl. Energy, 2013)

(untitled) - Hou, D.; Lin, D.; Ding, C.; Wang, D.; Wang, J. (Sep. Purif. Technol., 2017)

(untitled) - Hou, D.; Ding, C.; Fu, C.; Wang, D.; Zhao, C.; Wang, J. (Desalination, 2019)

(untitled) - Dong, Z.-Q.; Wang, B.-J.; Ma, X.-h.; Wei, Y.-M.; Xu, Z.-L. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Huang, Y.-X.; Wang, Z.; Hou, D.; Lin, S. (J. Membr. Sci., 2017)

(untitled) - Lee, E.-J.; An, A. K.; He, T.; Woo, Y. C.; Shon, H. K. (J. Membr. Sci., 2016)

(untitled) - Liao, Y.; Wang, R.; Fane, A. G. (Environ. Sci. Technol., 2014)

(untitled) - Prince, J. A.; Singh, G.; Rana, D.; Matsuura, T.; Anbharasi, V.; Shanmugasundaram, T. S. (J. Membr. Sci., 2012)

(untitled) - Yang, F.; Efome, J. E.; Rana, D.; Matsuura, T.; Lan, C. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Li, H.; Shi, W.; Zeng, X.; Huang, S.; Zhang, H.; Qin, X. (Sep. Purif. Technol., 2020)

(untitled) - Elmarghany, M. R.; El-Shazly, A. H.; Rajabzadeh, S.; Salem, M. S.; Shouman, M. A.; Nabil Sabry, M.; Matsuyama, H.; Nady, N. (Membranes, 2020)

(untitled) - Fiorenza, R.; Bellardita, M.; D’Urso, L.; Compagnini, G.; Palmisano, L.; Scirè, S. (Catalysts, 2016)

(untitled) - Adams, L. K.; Lyon, D. Y.; Alvarez, P. J. J. (Water Res., 2006)

(untitled) - Chang, X.; Zhang, Y.; Tang, M.; Wang, B. (Nanoscale Res. Lett., 2013)

(untitled) - Ognibene, G.; Cristaldi, D. A.; Fiorenza, R.; Blanco, I.; Cicala, G.; Scirè, S.; Fragalà, M. E. (RSC Adv., 2016)

(untitled) - Zhang, X.; Wang, D. K.; Diniz da Costa, J. C. (Catal. Today, 2014)

(untitled) - Leong, S.; Razmjou, A.; Wang, K.; Hapgood, K.; Zhang, X.; Wang, H. (J. Membr. Sci., 2014)

(untitled) - Ademola Bode-Aluko, C.; Pereao, O.; Kyaw, H. H.; Al-Naamani, L.; Al-Abri, M. Z.; Tay Zar Myint, M.; Rossouw, A.; Fatoba, O.; Petrik, L.; Dobretsov, S. (Mater. Sci. Eng., B, 2021)

(untitled) - Blanco, M.; Monteserín, C.; Angulo, A.; Pérez-Márquez, A.; Maudes, J.; Murillo, N.; Aranzabe, E.; Ruiz-Rubio, L.; Vilas, J. L. (Polymers (Basel, Switz.), 2019)

(untitled) - Wu, X.-Q.; Shao, Z.-D.; Liu, Q.; Xie, Z.; Zhao, F.; Zheng, Y.-M. (J. Colloid Interface Sci., 2019)

(untitled) - Wu, X.-Q.; Shen, J.-S.; Zhao, F.; Shao, Z.-D.; Zhong, L.-B.; Zheng, Y.-M. (J. Mater. Sci., 2018)

(untitled) - Salazar, H.; Martins, P. M.; Santos, B.; Fernandes, M. M.; Reizabal, A.; Sebastián, V.; Botelho, G.; Tavares, C. J.; Vilas-Vilela, J. L.; Lanceros-Mendez, S. (Chemosphere, 2020)

(untitled) - Yar, A.; Haspulat, B.; Üstün, T.; Eskizeybek, V.; Avcı, A.; Kamış, H.; Achour, S. (RSC Adv., 2017)

(untitled) - Li, Q.-H.; Dong, M.; Li, R.; Cui, Y.-Q.; Xie, G.-X.; Wang, X.-X.; Long, Y.-Z. (Carbohydr. Polym., 2021)

(untitled) - Campagnolo, L.; Lauciello, S.; Athanassiou, A.; Fragouli, D. (Water, 2019)

(untitled) - Rosman, N.; Wan Salleh, W. N.; Aziz, F.; Ismail, A. F.; Harun, Z.; Bahri, S. S.; Nagai, K. (Catalysts, 2019)

(untitled) - Kanjwal, M. A.; Chronakis, I. S.; Barakat, N. A. M. (Ceram. Int., 2015)

(untitled) - Chen, H.; Jiang, G.; Yu, W.; Liu, D.; Liu, Y.; Li, L.; Huang, Q.; Tong, Z.; Chen, W. (Powder Technol., 2016)

(untitled) - Zhong, Y.; Qiu, X.; Chen, D.; Li, N.; Xu, Q.; Li, H.; He, J.; Lu, J. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Liu, H.; Tang, X.; Liu, Q. (J. Water Health, 2014)

(untitled) - Fahimirad, S.; Fahimirad, Z.; Sillanpää, M. (Sci. Total Environ., 2021)

(untitled) - Parekh, S. A.; David, R. N.; Bannuru, K. K.; Krishnaswamy, L.; Baji, A. (Membranes, 2018)

(untitled) - Shalaby, T.; Hamad, H.; Ibrahim, E.; Mahmoud, O.; Al-Oufy, A. (Ecotoxicol. Environ. Saf., 2018)

(untitled) - He, J.; Wang, W.; Shi, R.; Zhang, W.; Yang, X.; Shi, W.; Cui, F. (Chem. Eng. J., 2018)

(untitled) - Yang, S.; Lei, P.; Shan, Y.; Zhang, D. (Appl. Surf. Sci., 2018)

(untitled) - Wang, J.; Wu, Y.; Yang, Z.; Guo, H.; Cao, B.; Tang, C. Y. (Sci. Rep., 2017)

(untitled) - Xie, L.; Shu, Y.; Hu, Y.; Cheng, J.; Chen, Y. (Chemosphere, 2020)